Crystal Structures and Properties of Large Protonated Water Clusters Encapsulated by Metal−Organic Frameworks - Duan, Chunying; Wei, Meilin; Guo, Dong; He, Cheng; Meng, Qingjin (Journal of the American Chemical Society, 2010)
A large ionic water cluster H(H2O)28 +, consisting of a water shell (H2O)26 and an encaged species H(H2O)2 + as a center core, was trapped in the well-modulated cavity of a porous metal−organic framework (MOF) {[Co4(dpdo)12(PMo12O40)3]−}∞ and structurally characterized. Degeneration of the protonated water cluster H(H2O)28 + into a smaller cluster H(H2O)21 + and recovery of H(H2O)28 + from the resulting H(H2O)21 + cluster in a reversible way demonstrated the unusual stability of the protonated water clusters H(H2O)28 + and H(H2O)21 + in the robust crystal host. Proton transport and proton/potassium ion exchange through the channels of the crystal host have been investigated by a well-established fluorometry method. X-ray fluorescence experiments and X-ray structural analyses of the exchanged crystals confirmed the occurrence of the proton/potassium ion-exchange reaction and the transformation of the protonated water cluster H(H2O)28 + to an ionic cluster K(H2O)27 +. Comparison of the H+/K+ exchange of H(H2O)28 + with that of its neighboring protonated water cluster H(H2O)27 + suggested that the abundance of hydrogen bonds associated with the hydronium/water cluster in the H(H2O)28 + cluster was essential for proton transport through the Grotthuss mechanism. On the basis of the results, our porous network could be described as a synthetic non-peptide ion channel, in terms of not only structural features but also the functions addressed. Direct observation of the structures of various large ionic water clusters trapped by porous MOFs, coupled with the proton/ion-exchange processes and the reversible dehydration/rehydration, provided valuable insights into the aqueous proton transfer and its mobility pertaining to the large protonated water clusters in the condensed phase.